Psychological preparedness of Special Malaysia Assistance and Rescue Team (SMART) for disaster response - Abdullah, Mohd (2001)
The rescue personnel deployed at the scene of disasters are susceptible to psychological consequences, which may affect the rescue team's response preparedness. SMART, being new to the search and rescue environment may also be subjected to these stressful consequences. This study is to determine the SMART's psychological preparedness based on Psychological Performance Profile developed by Asken (1993). The significant mean difference in psychological performance between the personnel of Bomba, Police and the Army that form the team is also identified. The study is also to evaluate the personnel perception of their level of confidence in performing various search and rescue operations. A total of 81 out of 85 SMART personnel were requested to complete questionnaires which was then analyzed using Statistical Package for Social Sciences. Cronbach's Alpha was used to analyze the internal consistence reliability of the instrument. The mean of the psychological skill variables were tabulated and plotted on graph to determine the level of psychological preparedness. The study reveals that the team only attains a fair level of psychological preparedness i.e. at the level of 'no commendations coming yet' (Asken 1993). There are also a slight difference in the mean of psychological performance and confidence in.performinq search and rescue operations between the personnel of the three departments that form the team.